Enhancing Forest Safety: Sensor-Assisted Detection and Prevention of Wildfires - Bhoir, Akshada; Ghone, Gayatri; Chavhan, Pranali; Khedkar, Vijayshri (International Conference on Computing Communication Control and Automation (Online), 2024)
This paper presents integrated forest fire detection and prevention system leveraging advanced sensor technologies, satellite monitoring, and UAVs. Data analytics and machine learning enhance accuracy, minimizing false alarms. Efficient communication with emergency services, public awareness campaigns, and community involvement are integral. The system aims to provide early detection, rapid response, and effective mitigation of wildfires, ensuring the safety of ecosystems and human communities. They cost more in India. In this paper we have discussed the effects of forest fires on India's biodiversity, forest species, climate changes and soil properties along with the different approaches the Indian government has taken to prevent and control forest fires. The forest fires economic impact is estimated to be over INR 1101 crore/year. By observing this we try to put light on this topic.